2018
DOI: 10.1159/000491993
|View full text |Cite
|
Sign up to set email alerts
|

Can Fetal Umbilical Venous Blood Be a Reliable Source for Admission Complete Blood Count and Culture in NICU Patients?

Abstract: Background: Minimizing initial neonatal blood draws and their associated pain is important. The placenta has ample fetal blood that is otherwise discarded; obtaining admission laboratory evaluations from fetal umbilical venous blood (FUVB) may provide a suitable alternative. Objective: We hypothesized that obtaining an aerobic bacterial blood culture (BCX) and a complete blood count with manual differential (CBC/diff) from FUVB is feasible and yields results comparable to those obtained directly from the neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 28 publications
(48 reference statements)
1
22
2
1
Order By: Relevance
“…Notwithstanding these issues, our trial had a high enrolment rate (72%) when compared to similar studies. In our cohort, the rate of delayed cord clamping was much higher than previous studies (Carrol et al 8,13 . (29%) 15 (44%)).…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Notwithstanding these issues, our trial had a high enrolment rate (72%) when compared to similar studies. In our cohort, the rate of delayed cord clamping was much higher than previous studies (Carrol et al 8,13 . (29%) 15 (44%)).…”
Section: Discussioncontrasting
confidence: 72%
“…Most importantly, our study found a significantly higher UVB BC volume inoculum when compared to the neonatal BC volume in addition to a low rate of contamination. Previous studies evaluated the use of UVB BC for early onset sepsis, showing a variable contamination rate (0–12.5%) 8,9,13,15,17 . We had one false‐positive UVB BC, which happened early in the trial.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Information currently available about pediatric immunological development mainly derives from studies using the mouse model or human cord blood, both of which have limited translational applications (17)(18)(19). For example, clinical parameters in human cord blood, such as neutrophil and lymphocyte numbers, are rarely equivalent to neonatal and infant blood values (20)(21)(22)(23). In addition, information in the veterinary medicine literature describes the developmental immune system in companion and food-producing animals but is limited due to stark differences in physiology between these animals and humans.…”
Section: Introductionmentioning
confidence: 99%